Physicochemical, microbiological and sensorial characteristics of flour and prepared cookies from the reject cashew (Anacardium occidentale L.) neglected (Research, Society and Development, 2021)
Nowadays, one of the main objectives of biotechnological development of new products is linked to processes and methods improvement. In this sense, the aim of this work is to promote the sustainable development of the residue obtained from the cashew´s organic reject material aiming at to produce a target flour to be applied as a functional food. In fact, the nutritional composition of the cashew flour showed an important food profile related to fibers and carbohydrates. In relation to the prepared food as a simple possibility, cookies were produced, and its sensorial characteristics were carried out in individual booths, with 100 non trained evaluators. The results showed that the cookies demonstrated a satisfactory acceptance profile in several analyzed attributes. Concerning to the microbiological analysis, nonsignificant presence of microorganisms was detected. So, the processed cashew flour showed to be nutritionally acceptable and together with a good sensorial acceptance, can be considered as a suitable biomass to produce a large amount of bakery products.